2018
DOI: 10.1021/acs.jpcc.8b00994
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Colloidal IV–VI Core/Shell Heterostructured Nanocrystals

Abstract: Colloidal nanocrystals (NCs) have been at the forefront of scientific research and technological applications since their emergence in the 1980s. The limitations of single component NCs and the growing demand for wide electronic tunability switched the attention to core/shell nanoheterostructures (NHs). The NHs consist of at least two semiconductor compounds, exhibiting improved surface passivation of the cores and surplus electronic tunability beyond that gained by size confinement. Several synthetic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 108 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…One popular handle in the tuning of colloidal nanocrystal syntheses is the choice of ligand, which can influence the resulting size, , shape, , phase, and composition via coordination to various nanocrystal facets or by altering the chemical potential, solubility, or reactivity of precursors in the reaction. This synthetic control has been extended to the development of heterostructured or hybrid nanocrystals, , which allow for the integration of complementary or multifunctional properties into a single system. Ligand coordination can be exploited to control secondary growth, such as at the edges or on specific facets of a nanocrystal, allowing for fine-tuning of the properties and functionalities of hybrid nanostructures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One popular handle in the tuning of colloidal nanocrystal syntheses is the choice of ligand, which can influence the resulting size, , shape, , phase, and composition via coordination to various nanocrystal facets or by altering the chemical potential, solubility, or reactivity of precursors in the reaction. This synthetic control has been extended to the development of heterostructured or hybrid nanocrystals, , which allow for the integration of complementary or multifunctional properties into a single system. Ligand coordination can be exploited to control secondary growth, such as at the edges or on specific facets of a nanocrystal, allowing for fine-tuning of the properties and functionalities of hybrid nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary growth of shells onto nanocrystalline cores has been used to tailor and improve nanocrystal properties by passivating surface states, modulating carrier confinement, or improving chemical stability. ,,,, For example, the synthesis of core/shell nanocrystal heterostructures based on transition metal dichalcogenides has recently gained attention as a strategy for modulating their optical or electronic properties and for improving the catalytic or photocatalytic abilities. Shell growth in the synthesis of nanocrystal heterostructures relies on a complex balance of several reaction parameters, including ligand coordination and precursor reactivity, and is typically achieved with two- or multi-step syntheses, in which a second set of precursors is added into a solution containing the core nanocrystals. , ,,, ,, Such methods are often time consuming and difficult to scale up, making the design of one-step heterostructure syntheses highly desirable. Promisingly, recent studies have demonstrated that one-step seeded growth is possible through carefully controlled precursor conversion and reaction kinetics, , although a diverse range of core/shell architectures has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…While size has long been used as a way to tune the NC band gap to a desired value, recent years have seen the emergence of ternary and quaternary NCs, where varying cation or anion ratios (e.g., I− III−VI 11−13 or lead halide perovskites 14 shells or radial composition gradients can be used to change the carrier confinement in the NC core and therefore the band gap. 15 Significant shifts (in the meV−eV range) in the position of the energy levels of an NC relative to vacuum can be achieved by (i) changing the surface termination of the NCs 16−19 or (ii) positioning the NC(s) near an interface that causes charge transfer to/from the NC(s). 20 For example, the valence and conduction band onsets of a PbS NC thin film shift up to 1−2 eV because of different surface terminations, 16−19 an effect which stems from the sum of (i) the intrinsic molecular dipole of the terminating ligand and (ii) the surface dipole of the ligand-NC interface (Figure 2).…”
mentioning
confidence: 99%
“…While size has long been used as a way to tune the NC band gap to a desired value, recent years have seen the emergence of ternary and quaternary NCs, where varying cation or anion ratios (e.g., I–III–VI or lead halide perovskites) adds another dimension of control to band gap tunability. Furthermore, shells or radial composition gradients can be used to change the carrier confinement in the NC core and therefore the band gap …”
mentioning
confidence: 99%
“…5 With available pathways for the controlled synthesis of various shapes, sizes, and compositions of nanoscale objects (see for example reviews by van Embden et al 6 and Hyeon and co-workers 7-9 on various colloidal synthetic methods), scientists looked for ways to combine two (or more) nano-objects into hybrid nanostructures (HNS) and potentially obtain materials with new properties. Continuing with the QD example, varying the deposition of a second semiconductor crystal on the existing QD results in a hybrid semiconductor/semiconductor (SC/SC) interface; some synthesized examples include core/(multi) shell, [10][11][12][13][14][15][16][17][18] yolk/shell [19][20][21] and heterodimers (usually two or more quasi-spherical shapes forming a heterojunction [22][23][24] as well as acorn-style structures 25 ). When the QD serves as a seed for an anisotropic structure such as a rod, 26 tetrapod 26,27 or octapod, 28 more complex structures result, 29 where the seed (junction) and arm are different SCs.…”
Section: Introductionmentioning
confidence: 99%